Astragaloside IV (AS-IV) alleviates the malignant biological behavior of hepatocellular carcinoma via Wnt/β-catenin signaling pathway - Jiang, ZhongYu; Mao, Zhen (RSC advances, 2019)
Astragaloside IV (AS-IV) is an active substance isolated from Astragalus membranaceus (Fisch.) Bungede, which has been shown to have pharmacological effects in a variety of cancers. However, the effects of AS-IV in hepatocellular carcinoma (HCC) and its related mechanisms have been poorly understood. In this study, we explored the roles of AS-IV on HCC and the underlying signaling pathway. We reported that the appropriate concentrations of AS-IV (25, 50, 100 nmol l −1 ) significantly suppressed the proliferation and cell cycle of HepG2 and Hep3B cell lines whilst promoting apoptosis. Besides, a trans-well and wound healing assay showed that AS-IV could markedly inhibit the migration and invasion of HepG2 and Hep3B cells, the expression of E-cadherin was up-regulation but the expression of N-cadherin and vimentin was down-regulation, and the protein levels of cleaved-caspase-3, 9 were increased markedly compared with the corresponding control. Furthermore, animal model treatment revealed that AS-IV could effectively reduce tumor formation. Moreover, AS-IV also significantly weakened the expression of Wnt, β-catenin and TCF-4 in vitro and in vivo . Taken together, these results suggested that AS-IV inhibited the biological processes of HCC via regulating of the Wnt/β-catenin pathway.